Study of the asymmetry in auxis thazard (lacepede, 1800)(family: Scombridae) collected from the bay of Oman - L. Jawad; J. Al-Mamry; L. Al-Sharyani; N. Al-Dhaouri (ՀՀ ԳԱԱ հրատ.)
Fluctuating asymmetry (FA) which is defined as random deviation from perfect symmetry of an organism can be used to judge the viability of an organism and the possibility to survive in natural population. Ֆլուկտուացող ասիմետրիան (ՖԱ),ինչը որոշվում է որպես օրգանիզմի բացարձակ սիմետրիայից կամայական շեղում, կարող է օգտագործվել գնահատելու համար օրգանիզմի կենսունակությունը և բնական պոպուլյացիայում գոյատևելու կարողությունը: Флуктуирующая асимметрия(ФА), которая определяется как произвольное отклонение от идеальной симметрии организма, может быть использована для оценки жизнедеятельности организма.
Keywords: Biology; Zoology